Exotic cluster structures in the mean-field theory - Klatt, Michael; Ichikawa, T.; Iida, K.; Itagaki, N.; Maruhn, J. A.; Matsuyanagi, K.; Mecke, Klaus; Ohkubo, S.; Reinhard, Paul-Gerhard; Schuetrumpf, B. (Journal of Physics: Conference Series, 2013)
Investigations of exotic cluster-like phenomena in the framework of the Skyrme-Hartree-Fock approach are reported. The occurrence of highly excited isomeric states is discussed in connection with the question of their stability in static and time-dependent Hartree Fock (TDHF) calculations. We find rotational stabilization of a 4α chain structure in 16O occurring for a limited range of angular momenta. A toroidal configuration of 40Ca was also stabilized by rotation and provides a very interesting example of rotation about a symmetry axis with a strictly quantized total angular momentum. Finally we look at the formation of nuclear pasta phases in a time-dependent approach and their classification.
CRIS-Team Scopus Importer:2023-07-24